(NrOZWITOK P)QÆZNAWALXNOÇ SFERI OSOBISTOSTÆ MOLOD[OGO [KOLQRA NA UROKAH LÆTERATURNOGO ^ITANNQ (B/s)E - (NmITNIK(B, (No(B.,s; (N{WECX(B, (Ns(B.s; (NbURQK(B, (Ng(B.s (2017)
(NpODANO ZAWDANNQ DO P)QÆDRU^NIKA (B"(NlÆTERATURNE ^ITANNQ(B. 2 (NKLAS(B" ((NAWTOR(B: (NsAW^ENKO o(B. (Nq(B.).s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (Np)QÆZNAWALXNIJ ROZWITOKs)E -- (NZASOBAMIs -- (N^ITACXKA D)QÆQLXNÆSTXs)E -- (NMOLOD[)QÆ [KOLQRÆs)E; (Nl)QÆTERATURNE ^ITANNQs)E -- (NSISTEMA ZAWDANXs -- (NBLO^NAs -- (NPO^ATKOWA [KOLAs; (NP)QÆZNAWALXNIJ ROZWITOKs)E; (N^ITACXKA D)QÆQLXNÆSTXs)E; (NL)QÆTERATURNE ^ITANNQs)E; (NSISTEMA ZAWDANXs; (NL)QÆTERATURNÆ TWORIs)E; (NUKRA)QÇNSXKÆ PISXMENNIKIs)E; (NKAZKIs; (NPO^ATKOWA [KOLAs; 2 (NKLASs